The Effect of Tax Knowledge in Moderating the Connection between the Theory of Planned Behavior and Taxpayer Compliance - Wenni Wahyuandari; Aisyah Talithahandari (Institut Bisnis dan Informatika Kesatuan, 2025)
Tax compliance plays a vital role in maintaining Indonesia’s fiscal sustainability, as tax revenue remains the country’s primary source of income. However, challenges in ensuring consistent taxpayer compliance continue to arise despite various regulatory efforts by the government. This study aims to examine the influence of attitudes, subjective norms, and perceived behavioral control on taxpayer compliance within the framework of the theory of planned behavior, while also assessing the moderating effect of tax knowledge. Using a quantitative approach, data were gathered from 100 individual taxpayers through a structured questionnaire, and the analysis was conducted using SmartPLS 3.2.9 with the Structural Equation Modeling (SEM) technique. The findings reveal that attitudes, subjective norms, and perceived behavioral control significantly and positively affect taxpayer compliance. Furthermore, tax knowledge moderates these relationships, indicating that individuals with higher tax knowledge demonstrate more consistent and rational compliance behavior, as their understanding helps reduce the influence of external behavioral factors.